The Role of Entrepreneurial Capabilities in Enhancing Organizational Excellence - Zeravan Omar; Mehvan Yousif (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ, 2024)
The global competition, dynamic environment, and limited resources nowadays put great pressure on modern institutions, including private universities (PU). Accordingly, entrepreneurial capabilities are needed for the entire organization, effective tools, and keys capable of not only ensuring efficient use of resources but also responding to the rapid dynamics of today’s environment to achieve organizational excellence and improve the performance and suitability of top educational institutions. This study examined the role of entrepreneurial capabilities (EC) in enhancing organizational excellence (OE). The researchers used a descriptive-analytical approach and used the questionnaire as a tool for data gathering.  181 questionnaires out of 210 collected from respondents from heads of scientific departments in a number of private universities in the Kurdistan Region and have been analysed. Data were analysed using the PLS-SEM software version (4.0.7) and also by the SPSS software version (26). The results showed that entrepreneurial abilities (EC) were positively related to organizational excellence (OE), the results also indicated that entrepreneurial abilities (EC) had a positive effect on organizational excellence. Thus, the use of (EC) and (OE) of private universities that are primarily used in private environments will contribute significantly to the knowledge management of those universities. The study suggested that more samples should be included in future studies, and the institution should be used as the unit of analysis. Discussing the level of the hierarchy at which organizational excellence and entrepreneurship are most beneficial to managers is another tool for future research in this field.